S142 Investigating patterns in 24 hours of coughing. (2nd December 2011) - Dockry, R J; Sunger, K; Marsden, P; Kelsall, A; Decalmer, S; Powley, W; Murdoch, R; Woodcock, A; Smith, J A
Abstract : Introduction and Objectives: Ambulatory 24 h cough monitoring is a relatively new technique, and so far few studies have investigated hourly variation in cough frequency. We analysed data from previous studies in three different disease groups to compare patterns throughout the day. Methods: We studied chronic cough (duration>8 weeks) [n=70, median age 58 yrs (IQR 49–64), 67.1% female], acute cough in otherwise healthy volunteers (duration <3 weeks) [n=56, median age 22 yrs (IQR 21–25.5), 62.5% female] and physician diagnosed asthma [n=58, median age 58.5 yrs (IQR 52–67.8), 63.8% female]. Subjects wore a cough monitor (Vitalojak) for 24 h and median numbers of coughs in each hour were manually counted and plotted against the actual time of day. Results: The asthmatic group had significantly lower total cough rates compared with the other groups (geometric mean 2.3 coughs/hr (SD±3.3); chronic cough 13.1 (±2.7); acute cough 8.9 (±2.63); p<0.001). Abstract S142 figure 1 shows the median coughs in each hour of the day (interquartile ranges). The chronic and acute cough groups show a very similar cough frequency and pattern, with two peaks during the daytime, despite substantial variability. The asthma group show a similar pattern but with much lower counts. For all diagnosis coughing practically ceases overnight. Conclusions: These data suggest that cough frequency in acute and chronic cough are remarkably similar, implying similar mechanisms may be driving coughing in these conditions, unlike in asthma where cough frequency is much lower. However all groups show similar fluctuations in hour to hour pattern of daytime cough and effective suppression of coughing during sleep, indicating behaviour has an important influence.